2009
DOI: 10.3844/ajidsp.2009.294.300
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Novel Sterilization Approach for the Pathogenic Staphylococcus aureus Bacteria

Abstract: Problem statement: Decontaminating meat surfaces has been the big concern of meat industry. Thus, various intervention strategies have been studied to reduce the level of bacteria on animals' carcass surfaces. Approach: Mixture of different concentrations 1, 1.5 and 2% of acetic, lactic, propionic and formic acids at 1:1 ratio were spray washed on inoculated meat to evaluate their efficacy in reducing numbers of Staphylococcus aureus on meat tissue at 4±1°C. The beef pieces were decontaminated with hot water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The target pH values for protein solubilization were pH 2.5, 3.0, 11.5, and 12.0. The acids tested were glacial acetic acid (AA; Fisher Scientific, Fairlawn, N.J., U.S.A.) and a combination of glacial L‐Lactic acid (85%, EMD Chemicals, the Netherlands) and formic acid (88%, Mallinckrodt Chemicals, the Netherlands) (F&L) at a 1 : 1 ratio (Mohammed and others ) was added to sterile distilled water at 30 to 70 mL vol/vol. The fish slurry was brought to the target solubilization pH (2.5, 3.0, 11.5, or 12.0) with the addition of the respective organic acid or 10 N sodium hydroxide (NaOH) and homogenized (PowerGen 700, Fisher Scientific, Pittsburgh, Pa., U.S.A.) until the pH stabilized (approximately 10 min).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The target pH values for protein solubilization were pH 2.5, 3.0, 11.5, and 12.0. The acids tested were glacial acetic acid (AA; Fisher Scientific, Fairlawn, N.J., U.S.A.) and a combination of glacial L‐Lactic acid (85%, EMD Chemicals, the Netherlands) and formic acid (88%, Mallinckrodt Chemicals, the Netherlands) (F&L) at a 1 : 1 ratio (Mohammed and others ) was added to sterile distilled water at 30 to 70 mL vol/vol. The fish slurry was brought to the target solubilization pH (2.5, 3.0, 11.5, or 12.0) with the addition of the respective organic acid or 10 N sodium hydroxide (NaOH) and homogenized (PowerGen 700, Fisher Scientific, Pittsburgh, Pa., U.S.A.) until the pH stabilized (approximately 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…When acetic, lactic, propionic, and formic acid were combined 1 : 1 at 1%, 1.5%, and 2% concentrations and sprayed onto beef carcasses, significant reductions of Staphylococcus aureus were achieved (Mohammad and others ). Moreover, the most lethal combination was with 1 : 1 lactic and formic acids at all concentrations (Mohammad and others ). These findings demonstrate the bactericidal potential of using combinations of organic acids in the ISP process; however, the effect of organic acids on protein and lipid recovery, as well as protein composition and functionality, would need to be determined.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When acetic, lactic, propionic and formic acid were combined 1:1 at 1%, 1.5% and 2% concentrations and sprayed onto beef carcasses, significant reductions of Staphylococcus aureus were achieved (Mohammad et al, 2009). Moreover, it was shown that the most lethal combination was with 1:1 lactic and formic acids at all concentrations (Mohammad et al, 2009). These findings demonstrate the bactericidal potential of using organic acids and combinations of organic acids in the ISP process.…”
Section: Fish Proteinmentioning
confidence: 70%
“…on whole chicken carcasses when sprayed on the carcasses and when dipped into the acid blend for 5 seconds (Laury et al, 2009). When acetic, lactic, propionic and formic acid were combined 1:1 at 1%, 1.5% and 2% concentrations and sprayed onto beef carcasses, significant reductions of Staphylococcus aureus were achieved (Mohammad et al, 2009). Moreover, it was shown that the most lethal combination was with 1:1 lactic and formic acids at all concentrations (Mohammad et al, 2009).…”
Section: Fish Proteinmentioning
confidence: 99%